FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN LANSIA RAWAT INAP DI RSUD INCHE ABDOEL MOEIS SAMARINDA BERDASARKAN DIMENSI HCAHPS - Fajar Prianto Nugroho; Iwan M. Ramdan; Riyan Ningsih (Forind Press, 2026)
Elderly patient satisfaction is a crucial indicator of inpatient care quality. This study aims to analyze the relationship between each dimension of HCAHPS with the level of satisfaction of elderly inpatients at I.A. Moeis Regional General Hospital, Samarinda, and to identify the most dominant factors through multiple linear regression analysis. A cross-sectional design was employed with a sample of 170 elderly patients (≥60 years) admitted to RSUD Inche Abdoel Moeis Samarinda (January-December 2024). Consecutive sampling was used. The instrument was an adapted HCAHPS questionnaire, subjected to validity and reliability tests. Statistical analysis included descriptive, bivariate (Spearman's Correlation), and multivariate (Multiple Linear Regression) analyses after checking classic assumptions. Significance level was set at p < 0.05. Respondents (n = 170) had a mean age of 66.8 years (SD 4.3); 50.6% were female. Perceptions of nurse communication, doctor communication, hospital environment, overall care experience, and post-discharge information were generally very positive. Satisfaction distribution: 85.9% high, 11.8% moderate, 2.4% low. Bivariate analysis revealed that only nurse communication was significantly correlated with satisfaction (r = 0.427; p < 0.001). The regression model indicated nurse communication as the sole significant predictor (B = 0.455; p < 0.001), explaining 33.8% of the variance in satisfaction (R2 = 0.338). Communication is the most dominant factor associated with inpatient elderly patient satisfaction. Implication: enhancing nurses' interpersonal communication skills (empathy training, listening skills, geriatric communication).